Alternative sample diluents in bioanalytical LC–MS. (December 2013) - David, Victor; Cheregi, Mihaela; Medvedovici, Andrei
The problem of sample diluent in bioanalytical LC–MS is reviewed with a special focus on large-volume injections and non-miscible solvents with mobile phase components. These issues are related to the sample preparation approach, which in many instances provides the sample diluent before injecting this into the chromatographic column. The sample volume influences the quantitation limit of the chromatographic method, while its nature may influence the retention process of the injected analytes. The literature reports a few papers that are focused on alternative sample diluents in bioanalytical LC–MS that are generally non-miscible with mobile phase. The principle of this approach and some of its current bioanalytical applications from literature are discussed. However, more applications and more publications from HPLC users and vendors are expected in this field, which could prove its analytical importance and potential in bioanalysis.